The Interplay of Poverty and Literacy: A Case Study of a Woman in Rural Nepal - Pandey, Shiv Ram (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This article presents on the interplay of poverty and literacy: A case study of a woman in rural Nepal. It follows a qualitative research method and case study design to receive data from a single sample population. The participant was selected purposively. The main purpose of this study was to explore how poverty and literacy have brought metamorphosis in the life of a participant of this study. The site of the study is Palungtar Municipality, 9, Mirkot, Gorkha. Interview and observation were used as tools of the study to obtain data from the participant. Honesty and confidentiality were duly followed during data collection process. Data were analyzed inductively. The study revealed that literacy created awareness and consciousness in the life of a participant. Literacy is the symbol of gradual development for survival and political and social involvement in her life. Literacy teaches her to be independent and it gives rise to her personal growth. It gives influence on involvement, power and position. More importantly, literacy provides her freedom. The study explored that poverty is the hindrance to progress and it teaches her to do struggle and to make progress in her life.